Quantile-specific heritability of sibling leptin concentrations and its implications for gene-environment interactions - Williams, Paul T. (Sci Rep, 2020)
“Quantile-dependent expressivity” occurs when the effect size of a genetic variant depends upon whether the phenotype (e.g., leptin) is high or low relative to its distribution. Leptin concentrations are strongly related to adiposity, whose heritability is quantile dependent. Whether inheritance of leptin concentrations is quantile dependent, and whether this explains the greater heritability in women than men in accordance with their greater adiposity, and explains other gene-environment interactions, remains to be determined. Therefore, leptin and leptin receptor concentrations from 3068 siblings in 1133 sibships from the Framingham Heart Study Third Generation Cohort were analyzed. Free leptin index (FLI) was calculated as the ratio of leptin to soluble leptin receptor concentrations. Full-sib (β(FS)) regression slopes were robustly estimated by quantile regression with nonparametric significance assigned from 1000 bootstrap samples. The analyses showed β(FS) increased significantly with increasing percentiles of the offspring’s age- and sex-adjusted leptin distribution (P(linear) = 0.0001), which was accelerated at the higher concentrations (P(quadratic) = 0.0003). β(FS) at the 90th percentile (0.418 ± 0.066) was 4.7-fold greater than at the 10th percentile (0.089 ± 0.032, P(difference) = 3.6 × 10(−6)). Consistent with quantile-dependent expressivity, the β(FS) was greater in female sibs, which was attributable to their higher leptin concentrations. Reported gene-environment interactions involving adiposity and LEP, LEPR, MnSOD, PPARγ, PPARγ2, and IRS-1 polymorphisms were consistent with quantile-dependent expressivity of leptin concentrations. β(FS) for leptin receptor concentrations and free leptin index also increased significantly with increasing percentiles of their distributions (P(linear) = 0.04 and P(linear) = 8.5 × 10(−6), respectively). In conclusion, inherited genetic and shared environmental effects on leptin concentrations were quantile dependent, which likely explains male–female differences in heritability and some gene-environment interactions.